Opportunity or Threat: Dissecting Tensions in a Post‐Carbon Rural Transition. Issue 1 (6th October 2015) - Lennon, Mick; Scott, Mark
Abstract: The deployment of renewable energy technologies represents a highly visible and contested indicator of rural change in terms of the function and appearance of rural places. In this article, we examine how notions of rurality and place intersect with macro‐level objectives for reducing carbon emissions, and how competing storylines underpin opposing and supporting coalitions in the deployment of wind energy projects. The article explores a series of recent controversial proposals for mega‐wind energy projects in the Irish midlands driven by energy companies seeking to take advantage of an Irish‐UK intergovernmental agreement to export green energy from Ireland to assist the UK in meeting its renewable energy targets. To examine these issues we develop and apply an interpretive approach to policy analysis inspired by the work of Laclau and Mouffe on the role of signifiers, antagonistic narratives and the constitutive outside. We identify how opposing and supporting discourses talk 'past one another' by framing narratives through different spatial referents (national versus local) and competing conceptualisation of the rural 'resource'. This inhibits the potential to imagine alternative post‐carbon rural trajectories.